Manajenem Kepala Sekolah Dalam Penanaman Sikap Disiplin Siswa - Wakidi Wakidi (Tadzkirah : Jurnal Pendidikan Dasar, 2021)
ABSTRACT Discipline is an order that can regulate the order of individual and group life. Discipline is the ability to control oneself in the form of not doing something, behavior and education that is not appropriate and contrary to something that has been determined. Furthermore, in an effort to inculcate student discipline in schools, it is very necessary to have a mature strategy carried out by school principals so that graduates from these educational institutions have strong attitude values. This research is a qualitative research. Data collection methods used are interviews, observation and documentation. The main sources in this research are principals, educators and education staff, while the secondary sources in this study are relevant books and data analysis techniques from this study using qualitative descriptive analysis techniques. Based on the results of the research data analysis, it can be concluded that the management efforts carried out by the principal in instilling student discipline are as follows: 1) Making school rules, 2) Arranging the physical environment, 3) Structuring the educational environment, 4) Cultivating togetherness, 5) Be a role model for students, 6) Giving sanctions for violations, 7) Coaching by habituation, 8) Coaching through motivation.